The relationship between junk food consumption and the growth and development of preschool children - St Hasriani; St Nurbaya; Windy Khaerati (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: The increasing consumption of junk food among preschool children has raised concerns regarding its potential impact on growth and development. Ultra-processed foods are typically high in calories, sugar, fat, and salt but low in essential nutrients required for optimal child health. Purpose: This study aimed to determine the association between a history of junk food consumption and growth as well as developmental status among preschool children. Method: A quantitative study with a cross-sectional design was conducted involving preschool children aged 3–5 years. Junk food consumption history was obtained through questionnaires. Growth status was assessed using the weight-for-height index, while development was measured using the Pre-Screening Developmental Questionnaire. Data were analyzed using the Chi-square test with a significance level of 0.05. Results: The analysis showed a significant association between junk food consumption and growth status (p < 0.05), indicating that higher intake was related to less favorable anthropometric outcomes. However, no significant relationship was found between junk food consumption and developmental status (p > 0.05). Most children demonstrated appropriate development despite moderate levels of junk food intake. Conclusion: Junk food consumption is linked to children’s growth but not directly associated with developmental outcomes. Growth and development are influenced by multiple interacting factors beyond diet alone. Suggestion: Future studies should include larger samples and additional variables such as socioeconomic conditions, parenting practices, and physical activity to better understand determinants of child health.